Analysis of lodging parameters in aromatic rice - Shahidullah, S. M.; Musa, Mohamed Hanafi; Md Ashrafuzzaman,; Md Kamal Uddin,; Meon, Sariah (2009)
The research work was conducted with 10 rice germplasm during T. Aman (wet season), 2004, at Bangladesh Rice Research Institute, Gazipur, to assess the different lodging concerned parameters and their interrelationships. A great extent of diversity among aromatic rice genotypes was observed in respect to canopy architecture and lodging related characters. Minimum seedling height was 30cm for BR39 and the maximum was 47cm for Hatisail. Variations were found in the cultivars regarding penultimate and flag leaf angles and dimensions of both the leaves. Maximum plant height was recorded to be 153cm in Baoi jhak and the minimum was 100cm in BR28. The longest panicle was observed in Nizersail (27cm) and shortest in Hatisail (21cm). The range of culm diameter was 4.0-4.7mm and culm thickness was 0.40-0.51mm. Rice cultivars varied for bending moment from 812gcm (BR28) to 2263 gcm (Doiar guro). Lodging index was at a minimum 2.7 in BR28 and a maximum 11.28 in Sugandha-1. Plant height exhibited positive correlation with panicle exertion and internode lengths, and hence lodging index. Lodging index was found to have a negative relationship with breaking strength. In path analysis, bending moment projected highest positive direct effect on lodging index.